2018
DOI: 10.1186/s12935-018-0634-8
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of intratumor immune-microenvironment in colorectal cancers with extranodal extension of nodal metastases

Abstract: BackgroundNo data is available on the molecular background of the extra-nodal extension (ENE) of lymph node metastasis (LN) in colorectal cancer (CRC).MethodsA series of 22 ENE-positive CRCs was considered and three samples per case were selected (the primary CRC, an ENE-negative and an ENE-positive metastatic LN). Samples (n = 66) were analysed by immunohistochemistry for PD-L1, CD4, CD8, CD68 and CD80. Fifteen out of twenty-two cases were further profiled through a hotspot multigene mutational custom panel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…BRAF-mutated (BRAFmt) CRCs have specific clinicopathological and molecular features [14][15][16][17][18], identifying a distinct subset with aggressive phenotype and poor outcome ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…BRAF-mutated (BRAFmt) CRCs have specific clinicopathological and molecular features [14][15][16][17][18], identifying a distinct subset with aggressive phenotype and poor outcome ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Despite some techniques like MRI texture analysis or phenotype determinations that have been introduced to roughly assess the TDs status, an accurate prediction shaping personalized TDs features remains an arduous task. [31][32][33][34] A predictive nomogram is currently an efficient tool to improve preoperative TDs prediction and investigate related mechanisms. Our nomogram incorporated six-gene risk score system (miR-614, miR-1197, miR-4770, miR-3136, miR-3173, and miR-4636) and exhibited satisfactory performances in high-risk group identification.…”
Section: Discussionmentioning
confidence: 99%
“…There is no final conclusion about the effect of the number of cancer nodules on prognosis. Studies have shown that the count of CD8-positive T lymphocytes in cancer nodules of patients with CRC is significantly higher than that of tumor tissue, 28 suggesting that changes in the tumor microenvironment are important for the generation of cancer nodules. The dMMR status has an important effect on the tumor microenvironment, 29 suggesting that the generation of cancer nodules may be related to the microsatellite status.…”
Section: Discussionmentioning
confidence: 99%